Comparison of Prophylactic Infusion of Phenylephrine and Ephedrine for the Prevention of Hypotension in Elective Lower Segment Caesarean Section Under Spinal Anesthesia. - Harekrishna Ray; Madhumita Biswal; Basanta Kumar Pradhan; Sujata Mishra; Mangal Charan Murmu (International Journal of Pharma and Bio Sciences, 2024)
Hypotension is the primary adverse outcome associated with spinal anesthesia during cesarean delivery, potentially leading to adverse effects in mothers and acid-base imbalances in newborns. It is widely acknowledged that efficient intervention is crucial to prevent any negative impact on fetal birth. Administering anesthesia to pregnant women requires the highest level of care, as the anesthesiologist must consider the well-being of both the mother and the fetus. The primary side effect of spinal anesthesia during a cesarean birth, which could lead to unfavorable symptoms in the mother and acid-base consequences in the newborn, is hypotension. Phenylephrine and ephedrine are known for their efficacy in preventing hypotension following spinal anesthesia. This study aims to assess the effectiveness of prophylactic infusions of phenylephrine and ephedrine in averting hypotension during elective lower-segment cesarean sections under spinal anesthesia. Examining the impact of prophylactic infusions of phenylephrine and ephedrine as vasopressors. Treatments during Unconsciousness originating in the spinal cord for cesarean sections and their impact on infant outcomes were investigated. We found that both Ephedrine and phenylephrine effectively managed systolic, diastolic, and mean arterial pressure. The ephedrine group needed a significantly higher number of additional boluses than the phenylephrine group (p value<0.001). The phenylephrine group exhibited a more favorable pH and lower acidosis levels than the ephedrine group (p-value 0.05). Prophylactic administration of phenylephrine at a dosage of 15 mcg/min proved more effective in sustaining arterial blood pressure following spinal anesthesia for cesarean delivery than Ephedrine at 1.5 mg/min, and this effected reduced acidosis in newborns.